Report on Industrial Organisation National Committee on the Development of Backward Areas - Planning Commission (Planning Commission, 1981)
A Central organisation is no more capable of supporting the promotion and development of the so many types of industries that can be usefully promoted in the present economy. It is now necessary that the States take over the basic responsibility for the development and encouragement of small industries. But this responsibility cannot be discharged effectively without the active cooperation and an umbrella role on the part of the central organisation created for the development and support of industry.
Planning Commission, Government of India